Pectin/alginate aerogel containing ZnO produced from beetroot extract mediated green synthesis for potential applications in food packaging - Stefania Mottola; Gianluca Viscusi; Gianmaria Oliva; Giovanni Vigliotta; Stefano Cardea; Giuliana Gorrasi; Iolanda De Marco (Journal of CO2 Utilization)
In this work, pectin aerogels loaded with zinc oxide (ZnO) were produced for a possible application in food packaging. Using a green synthesis procedure, ZnO nanoparticles were obtained via beetroot extract as a reducing, capping, and stabilizing agent; the obtained ZnO particles, with an average size of 300 nm, were loaded into pectin/alginate-based aerogels. Supercritical drying was used to produce the biopolymers-based aerogels, which were initially formulated with different polymer concentrations (2 wt% and 4 wt%) and various ratios between pectin and alginate (9:1, 7:3, 1:1) to identify the optimal configuration that would guarantee a balance between strength and morphology, resulting in better properties in the final structure. The aerogels enriched with different ZnO percentages (5 %, 10 %, and 15 %) were later produced. The aerogels showed a porous structure with uniform pore size distribution, influenced by the ZnO loading. The liquids’ absorption test of the samples assessed that higher concentrations of ZnO could reduce the available surface area, limiting the aerogels’ absorption capacity. The potent antimicrobial activity of ZnO and pectin/alginate aerogels against the non-pathogenic Escherichia coli and the pathogenic Staphylococcus aureus strains was demonstrated using a minimum lethal dose, highlighting the possibility of employing such materials in food packaging.